2022
DOI: 10.1101/2022.06.21.497008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pancreatic tumors activate arginine biosynthesis to adapt to myeloid-driven amino acid stress

Abstract: Nutrient stress in the tumor microenvironment requires cancer cells to adopt adaptive metabolic programs to maintain survival and proliferation. Therefore, knowledge of microenvironmental nutrient levels and how cancer cells cope with such nutrition is critical to understand the metabolism underpinning cancer cell biology. Previously, we performed quantitative metabolomics of the interstitial fluid (the local perfusate) of murine pancreatic ductal adenocarcinoma (PDAC) tumors to comprehensively characterize nu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…Nevertheless, it is provocative to consider that general tissue homeostatic nutrient maintenance mechanisms are preserved in tumors, and that cancer cells may retain some dependence on nutrients defined by the adjacent origin tissue. To this end, it is notable that the metabolites found in RCC TIF differ from those reported in mouse pancreatic ductal adenocarcinoma (PDAC) TIF 14,49 , and from those found in interstitial fluid derived from mouse brain and mammary fat pad tissue 8 . Findings from analysis of PDAC TIF from tumors implanted in different tissue sites also noted differences in metabolite levels 14 , supporting the notion that cancer must adapt to a specific tissue nutrient environment rather than determine the majority of nutrients present.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Nevertheless, it is provocative to consider that general tissue homeostatic nutrient maintenance mechanisms are preserved in tumors, and that cancer cells may retain some dependence on nutrients defined by the adjacent origin tissue. To this end, it is notable that the metabolites found in RCC TIF differ from those reported in mouse pancreatic ductal adenocarcinoma (PDAC) TIF 14,49 , and from those found in interstitial fluid derived from mouse brain and mammary fat pad tissue 8 . Findings from analysis of PDAC TIF from tumors implanted in different tissue sites also noted differences in metabolite levels 14 , supporting the notion that cancer must adapt to a specific tissue nutrient environment rather than determine the majority of nutrients present.…”
Section: Resultsmentioning
confidence: 96%
“…Recent studies have found that arginine is depleted to very low levels in murine pancreatic cancer TIF 14,49,50 , a phenomenon facilitated by myeloid-derived arginase activity 49 . Of note, arginine is not significantly depleted in KIF or TIF from RCC patients compared to plasma, although levels of related urea cycle metabolites are reduced in TIF and KIF compared to plasma (Figure 2E).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of SLC7A5 may sensitize tumors to an arginine depletion agent such as ADI-PEG20 and improve therapeutic efficacy. Beyond co-treatment with arginine depleting agents, the efficacy of SLC7A5 agents may reveal tumors with limited arginine availability in the TME 65,66 . Numerous studies have shown that JPH203 treatment slows tumor growth in xenograft models [67][68][69][70] .…”
Section: Discussionmentioning
confidence: 99%
“…Those include a dramatic drop in arginine and tryptophan [26]. The same group recently suggested in a preprint study, that cultivating PDAC cells in a TIF‐based culture medium better recapitulated the transcriptomic in vivo gene signature of PDAC xenografts, which supports a chronic starvation state of these tumours associated with a constitutive activation of the amino‐acid response pathway [27]. These findings advocate for the use of TIF‐based media to understand tumour cell metabolism, particularly in this new era dedicated to developing alternative models to animals.…”
Section: Modelling the Nutritional Milieu Of Tumour Cellsmentioning
confidence: 94%